Kemiskinan Dan Distribusi Pendapatan Serta Solusinya Dalam Perspektif Islam - Moh Agus Sifa' (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2019)
Poverty means a situation where there is a need to work harder to meet their needs because of lack or weakness in the material. Due to material shortages, poor people have difficulty meeting nutritional needs, getting proper education, working capital and a number of others. Whereas in terms of distribution, it is a process that shows the distribution of goods from producers to the consumer society. As for dealing with poverty and income distribution, there are several possibilities that can overcome poverty in the Islamic concept as follows; a) Feeding. b) Infaq. c) Fidyah, d) State Responsibility. For distribution of income In order for distribution to provide adequate significance, it is necessary to consider the principles of distribution as follows: a) Principles of justice and equity, b) Principles of brotherhood and love, c) Principles of social solidarity Keywords: poverty, income distribution